The Effect of Asset Growth With Profitability and Company’s Value (Case Study: Coal Company was Listed in Bursa Efek Indonesia during 2014-2016 Period) - Nugroho, Mulyanto Nugroho (Archives of Business Research, 2018)
Indonesia as big country has also many industries. One of potential industry that is Indonesia had is coal field. In this research will test the effect of asset growth with profitability and company’s value in coal’s company. As population in this research is all of coal’s company which is listed in Bursa Efek Indonesia during 2014-2016 period. Purposive sampling method is utilized to take sample. Eight coal’s company were selected to be sample of this research. Analysis was conducted with inner, outer, and simultaneously model with Partial Least Square (PLS) program version 2.0. Result of this research are, firstly, asset growth has positive impacts significantly with profitability. Second, asset growth also has positive impacts significantly with company’s value. Third, profitability has negative impacts significantly with company’s value.